2019
DOI: 10.1039/c8ra09351b
|View full text |Cite
|
Sign up to set email alerts
|

Production of rhamnolipids with different proportions of mono-rhamnolipids using crude glycerol and a comparison of their application potential for oil recovery from oily sludge

Abstract: The use of efficient green cleaning agents, such as biosurfactants, is important in oil sludge treatment.Enhanced oil recovery from oily sludge by different rhamnolipids was comparatively evaluated. Using crude glycerol, the wild-type strain Pseudomonas aeruginosa SG and the recombinant strains P.aeruginosa PrhlAB and P. stutzeri Rhl produced 1.98 g L À1 , 2.87 g L À1 and 0.87 g L À1 of rhamnolipids, respectively. The three bacterial strains produced different rhamnolipid mixtures under the same conditions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Although the use of rhamnolipids in enhanced oil recovery has been tested before, until recently, the production of rhamnolipid variants and their efficiency in MEOR have become a research hotspot [16,17,18]. In this study, the rhamnolipid-producing strain P. aeruginosa YM4 was selected for its capacity to efficiently produce Rha-Rha-C 10 -C 10 as the major component with soybean oil and glycerol as carbon source.…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of rhamnolipids in enhanced oil recovery has been tested before, until recently, the production of rhamnolipid variants and their efficiency in MEOR have become a research hotspot [16,17,18]. In this study, the rhamnolipid-producing strain P. aeruginosa YM4 was selected for its capacity to efficiently produce Rha-Rha-C 10 -C 10 as the major component with soybean oil and glycerol as carbon source.…”
Section: Introductionmentioning
confidence: 99%
“…The mass spectrometer was in the negative ESI mode and the scanning mass range was from 200 to 900 m/z (mass to charge ratio). RL congeners were identified based on m/z and their relative proportions were calculated using the obtained area for each congener of RL by HPLC–MS (Haba et al 2014 ; Zhao et al 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, they may be used in various industries like pharmaceuticals, cosmetics, food and agriculture. Moreover, they are also used in enhanced oil recovery (EOR) and bioremediation of heavy metals and hydrocarbon pollutants (Zhao et al 2019 ). The use of chemical surfactants for enhancing oil recovery and biodegradation is unfavorable as they are toxic, expensive and may negatively impact the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that using crude glycerol for anaerobic production of rhamnolipids by P. aeruginosa is feasible. Previous studies reported aerobic production of rhamnolipids by P. aeruginosa using crude glycerol [39,40]. Using glycerol or crude glycerol, the rhamnolipids yields from P. aeruginosa were both lower under anaerobic conditions.…”
Section: Ftir Spectra Analysis Of Anaerobically Produced Rhamnolipids Using Glycerol and Nitratementioning
confidence: 95%